1999
DOI: 10.1177/090591999900900306
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care Guidelines: Finding a Common Ground

Abstract: Pressure to reduce overall transplant costs is one of the factors which has led to earlier hospital discharge and increased patient management challenges in outpatient and home care settings. Earlier discharge often contributes to decreased opportunity to provide and ensure comprehension of critical patient and family education, resulting in challenges for home care clinicians who are committed not only to patient and environmental assessments, but to helping assure patient and family understanding of and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Moreover, the authors of several studies have remarked that rehabilitation should start postoperatively within a few days and that its success or lack thereof can have a marked effect on outcomes (Juskowa et al, 2006;Templin and Janek, 2006;Korabiewska et al, 2007;Sanchez et al, 2007). Randolph and Scholz (1999) also comment that to reduce costs, patients are often discharged so quickly that there is little time for education or institution of self-care or rehabilitation. From our study we identified exercise as a part of the early rehabilitation program and this component is also supported by cardiovascular, biochemical, and muscle strength benefits shown by other studies (Juskowa et al, 2006;Korabiewska et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the authors of several studies have remarked that rehabilitation should start postoperatively within a few days and that its success or lack thereof can have a marked effect on outcomes (Juskowa et al, 2006;Templin and Janek, 2006;Korabiewska et al, 2007;Sanchez et al, 2007). Randolph and Scholz (1999) also comment that to reduce costs, patients are often discharged so quickly that there is little time for education or institution of self-care or rehabilitation. From our study we identified exercise as a part of the early rehabilitation program and this component is also supported by cardiovascular, biochemical, and muscle strength benefits shown by other studies (Juskowa et al, 2006;Korabiewska et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…19 Parenteral nutrition will be started after transplantation but patients will be gradually weaned from parenteral nutrition with concurrent increases in enteral feedings. 20 Parenteral nutrition may be resumed intermittently during periods of rejection or infection or if enteral feedings are not yet tolerated. Jejunal enteral feedings with a diluted elemental formula are generally initiated at 5 to 10 mL/hr.…”
Section: Advanced Nutrition Managementmentioning
confidence: 99%